De kunstprijzen Amsterdam 1998. - Samkalden, Robert (Amsterdam : AFK (Het Amsterdams Fonds voor de Kunst), 1998)
Ouwens, Kees ; Kuik, Dirkje ; de Jong, Oek ; de Vries, Klaas ; Prins, Annemarie ; Steenbergen, wouter ; Roeland, Jan ; van der Keuken, Johan ; van Lieshout, Joep ; Schröder, Rob ; Eekhout, Mick ; van Slobbe, Alexander ; Pontiac, Peter
Nederlands
boek